Using Digital Technologies in E-Services Bank Transformation in Uzbekistan - Umarova Malika Bakhtiyarovna (Scientific Trends, 2023)
E-banking services can be described as remote banking services for legal entities and individuals, depending on the legal status of their customers. Currently, modern services such as "Corporate Internet Banking", "Mobile Banking" and "SMS Banking" are provided among almost all commercial banks in Uzbekistan. Expanding the scope of Internet banking services for legal entities is also in constant focus. Current paper work focused on learning theoretical approaches of the reforms on this field. Main outcomes displayed in forms of graph, tabulation and road map.
Keywords: Commercial banks, e-bank, effectiveness, time management, service satisfaction.